Bone Substitutes in Orthopaedic Surgery: Current Status and Future Perspectives - Busch, André; Wegner, Alexander; Haversath, Marcel; Jäger, Marcus (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Bone replacement materials have been successfully supplied for a long time. But there are cases, especially in critical sized bone defects, in which the therapy is not sufficient. Nowadays, there are multiple bone substitutes available. Autologous bone grafts remain the “gold standard” in bone regeneration. Yet, donor-site morbidity and the available amount of sufficient material are limitations for autologous bone grafting. This study aimed to provide information about the current status in research regarding bone substitutes. We report on the advantages and drawbacks of several bone substitutes. At the end, we discuss the current developments of combining ceramic substitutes with osteoinductive substances.
Keywords: critical size bone defect; ceramic bone substitute; osteoconductive; osteoinductive